Does the Karoo population of Martial Eagles (Polemaetus bellicosus) have the potential to buffer the species? national decline? - Doherty, Jane (Department of Biological Sciences, 2024)
There has been a rapid decline in Martial Eagle (Polemaetus bellicosus) sightings across Sub-Saharan Africa, with the species recently up-listed to Endangered. However, in South Africa in recent decades, a population has become established in the Karoo, a largely treeless and semi-arid biome not considered favoured by the species in the past. This shift was likely to have been facilitated by electricity infrastructure, specifically large pylons, on which they now nest. In this study, we attempted a population viability analysis of this population. Our interest was to explore whether the Karoo population might be a source population and, if so, whether it could help buffer the national population from declines seen elsewhere. We used two longitudinal datasets: three years of detailed breeding data from 47 territories, collected through twice-yearly aerial surveys and quarterly on-the-ground monitoring (representing 137 breeding pair years); and tracking data from 19 birds (representing 27 years' data), from 2019 to 2021. We used these data to estimate breeding parameters and to estimate mortality rates for adults and non-adults. These estimates were then entered into the population simulation software, Vortex, creating four scenarios to take into account uncertainties in both our breeding and mortality estimates. The calculated rates of breeding attempt, breeding success and productivity were 53%, 80% and 42%, respectively. Maximum average annual adult and non-adult mortality rates (which assumed that all tracked eagles that disappeared had died) were 24% and 61%, respectively. The equivalent minimum rates (which assumed tag failures for offline birds that had not been confirmed dead) were 9% and 38%, respectively. Our models suggested that the Karoo sub-population will, at best, shrink by 10% per annum over the next 20 years. At worst, the population will shrink by 30% per annum. At these rates, and without immigration by individuals from other populations, the Karoo population will be close to extinction – if not already extinct – in two decades. Evidently, the Karoo population will not be able to buffer the species' national decline: it could even be a sink for eagles from source populations elsewhere. However, our models are highly sensitive to our survival rates which, because of our small sample size, may be relatively poorly estimated. We suggest that, in order to improve our understanding of the future population dynamics of this species, improved survival estimates should be obtained for the Karoo, as well as information on patterns of recruitment and dispersal by young eagles and adult floaters.